Harry Potter and the half-blood prince Bd 6 - Rowling, J. K.
Though the war against Voldemort is not going well, life at Hogwarts goes on, with the sixth-year students continuing their wizardly studies and trying to survive teen romantic dramas, while Harry himself probes ever more deeply into Voldemort's complex history.